Effect of tachykinins on ascending and descending reflex pathway in rat small intestine. - HAHN Andreas; STORR Martin; ALLESCHER Hans-Dieter (Acta Pharmacologica Sinica, 2016)
AIM: To examine the effect of tachykinins on the ascending reflex pathway in rat small intestine, we used different selective neurokinin (NK) receptor antagonists (RA): a) NK1-RA: GR-82334 and CP-96.345, b) NK2-RA: MEN-10.376 and L-659.877. The aim was further to investigate the effect of substance P (SP) on the ascending excitatory and descending inhibitory reflex pathway. METHODS: The whole segments of rat ileum (10 cm in length) were studied in an organ bath. Ascending contraction of circle muscle was elicited by anal electrical stimulation (3 Hz, 1 ms, 20 V) and measured as change of intraluminal pressure by a perfused manometric system 2 cm and 4 cm orad of the stimulation site. RESULTS: GR-82334 and CP-96.345 (NK1-RA) caused a significant dose-related inhibition of the oral contraction at a distance of 4 cm: GR-82334 [area: -10 % +/- 8 % (10 nmol/L); -29 % +/ -10 % (1000 nmol/L). P < 0.05, n = 10], CP-96.345 [area: -2 %+/- 6 %(0.1 nmol/L); -14 % +/- 10 % (10 nmol/L). P < 0.01, n = 8], whereas the contractile response at a distance of 2 cm was unaltered (n = 8). In contrast, MEN-10.376 and L-659.877 (NK2-RA) did not alter the amplitude or the area under the curve (n = 10). Neither the NK1- nor the NK2-receptor antagonists had a significant effect on the latency of the reflex response. SP showed a significant increase in the ascending contraction and the descending relaxation (n = 6, P < 0.01). CONCLUSION: These results demonstrate that blockade of NK1-receptors decreases the oral reflex response. Latency of the reflex response remains unchanged, indicating that the effect is not due to an action on interneurons. NK2-receptors do not take part in the ascending reflex in rat small intestine. SP increases the descending relaxant reflex response and ascending contraction.